ON THE RELIGIOUS AND SPIRITUAL LIFE OF THE ANCIENT POPULATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, the authors provide information about the religious and spiritual life of the ancient population. The authors emphasize that the ancient population was characterized by clan beliefs, totemic cults associated with natural phenomena, deification of nature, as well as shamanic beliefs mixed with animism and totemism. One of the most important aspects of these religious beliefs is that they have a unifying effect on communities.